Amelioration of Posttraumatic Osteoarthritis in Mice Using Intraarticular Silencing of Periostin via Nanoparticle‐Based Small Interfering RNA. Issue 12 (28th October 2021) - Duan, Xin; Cai, Lei; Pham, Christine T. N.; Abu‐Amer, Yousef; Pan, Hua; Brophy, Robert H.; Wickline, Samuel A.; Rai, Muhammad Farooq
Abstract : Objective: Recent evidence delineates an emerging role of periostin in osteoarthritis (OA), since its expression after knee injury is detrimental to the articular cartilage. We undertook this study to examine whether intraarticular (IA) knockdown of periostin would ameliorate posttraumatic OA in a murine model. Methods: Posttraumatic OA was induced in 10‐week‐old male C57BL/6J mice (n = 24) by destabilization of the medial meniscus (DMM), and mice were analyzed 8 weeks after surgery. Periostin expression was inhibited by small interfering RNA (siRNA) delivered IA using a novel peptide–nucleotide polyplex. Following histologic assessment of the mouse knee cartilage, the extent of cartilage degeneration was determined using Osteoarthritis Research Society International (OARSI) cartilage damage score, and severity of synovitis was also assessed. Bone changes were measured using micro–computed tomography. The effect and mechanism of periostin silencing were investigated in human chondrocytes that had been stimulated with interleukin‐1β (IL‐1β) with or without the IκB kinase 2 inhibitor SC‐514. Results: Periostin expression in mice with posttraumatic OA was significantly abolished using IA delivery of a peptide–siRNA nanoplatform. OARSI cartilage damage scores were significantly lower in mice receiving periostin siRNA (mean ± SEM 10.94 ± 0.66) compared to untreated mice (22.38 ± 1.30) and mice treated with scrambled siRNA (22.69 ± 0.87) (each P = 0.002). No differences in the severity of synovitis were observed. Subchondral bone sclerosis, bone volume/total volume, volumetric bone mineral density, and heterotopic ossification were significantly lower in mice that had received periostin siRNA treatment. Immunostaining of cartilage revealed that periostin knockdown reduced the intensity of DMM‐induced matrix metalloproteinase 13 (MMP‐13) expression and also diminished the phosphorylation of p65 and immunoreactivity of the aggrecan neoepitope DIPEN. Periostin knockdown also suppressed IL‐1β–induced MMP‐13 and ADAMTS‐4 expression in chondrocytes. Mechanistically, periostin‐induced MMP‐13 expression was abrogated by SC‐514, demonstrating a link between periostin and NF‐κB. Conclusion: IA delivery of the periostin–siRNA nanocomplex represents a promising clinical approach to mitigate the severity of joint degeneration in OA. Our findings may thus provide an unequivocal scientific rationale for longitudinal studies of this approach. Utilizing a cartilage‐specific gene‐knockout strategy will further illuminate the functional role of periostin in OA.